Worldwide disaster loss and damage databases: A systematic review - Sadegh Ahmadi Mazhin; Mehrdad Farrokhi; Mehdi Noroozi; Juliet Roudini; Seyed Ali Hosseini; Mohammad Esmaeil Motlagh; Pirhossein Kolivand; Hamidreza Khankeh (Wolters Kluwer Medknow Publications, 2021)
Nowadays, disaster databases have become a valuable tool for disaster risk management and health promotion and serve various purposes. The purpose of this study is to provide a systematic review of disaster databases in the world and to identify the objectives, information sources, criteria, and variables of disaster data registration in the world's reputable databases. To conduct review, all English-language articles published without a time limit until the end of September 2020 were extracted from the databases of Web of Science, PubMed, Scopus, Cochrane Library, Science Direct, Google Scholar, and Embase. Necessary information in the papers including study time, type of disasters, related databases, dimensions and indicators of global and regional databases were extracted by using a researcher-made questionnaire. A total of 22 studies have been reviewed to identify the dimensions and indicators of disaster databases worldwide. The main focus was on global and regional databases, mostly used at the level of scientific societies and disaster experts. After explanation, researchers highlighted each of the disaster databases, along with the main differences available among the existing databases. Some databases have well-defined data collection methods. Their knowledge is high quality and they can be used to create and improve a disaster database at other levels. Disaster database limitations include risk bias, time bias, accounting bias, threshold bias, and geographical bias. To support the right decisions to reduce disaster risk, it is necessary to complement existing global, regional, and national databases. Countries need to take action to set up national databases.